Hemoglobin Levels of Female Students Based On Fe Consumption and Breakfast Habits - Yuliani, Meda; Asri; Oktafiani, Hani; Hayati, Ning (Universitas STRADA Indonesia, 2020)
Background : Breakfast is the most important activity in fulfilling energy consumption and nutritional needs in a day, but there are still many adolescents who skip this habit. This problem causes reduced iron in the blood which results in anemia. Purpose : This study aims to analyze Hb levels in female students based on Fe consumption and breakfast habit. Method : This study used a descriptive analysis with 253 females as the respondents. The data was collected from March - July 2019. As much as 72 data respondents were analyzed by using simple random sampling technique. This study measured Hb and usied a checklist tool to determine HB levels based on consumption and breakfast habits. Results : The results from 72 respondents showed that almost 63 people (87%) have Hb content ≥12 g / dL, 47 people (65%) consumed Fe, and also 45 people (62%) have breakfast habits. In conclusion, most of 47 girls (65%) consumed Fe with an hb level of ≥12 g / dL, 45 people (62%) had the habit of having breakfast with Hb levels ≥12 gr / dL. Conclusion : The school and Public Health Center need to work together in dealing with female students who have low Hb levels. The role of parents is also important in fostering the students to consume iron and have breakfast habit.